SYSTEMATIC LITERATURE REVIEW OF POLICY GRIDLOCK - devrizon, devrizon; Kumorotomo, Wahyudi; Hadna, Agus Heruanto (Magister Ilmu Administrasi Publik, 2024)
This article systematically reviews academic research on policy gridlock (PG) to provide an overview of the development of PG in public administration (PA). This study analyzed 94 articles published between 1988 and 2022 using a systematic meta-analysis of literature reviews (SLRs) with Vosviewer software and a qualitative approach. This study finds the main research typologies in the PG literature, namely PG formation and PG completion. Our analysis also reveals that PG formation has a predominance in PG research. Meanwhile, the least published typology of PG is the completion of PG with sub-typologies, namely looking at the impact. Finally, we offer 25 future research directions to fit this typology. This study may be the first to use SLR analysis and qualitative analysis to generate detailed information about each typology of PG literature research in PA disciplines by measuring the number of publications over the last 30 years. The results of our review are limited to PG publications in the social sciences to focus on PA and policy studies and are derived from the Scopus database.